Diagnostics of Milling Head Using Acoustic Emission - Piórkowski, Paweł; Roszkowski, Andrzej; Szabla, Zofia (Manufacturing Technology Journal, 2025)
Monitoring and diagnostics of cutting tools are crucial for ensuring production efficiency and product quality in the machining industry. This study uses acoustic emission (AE) to non-invasively detect damage and monitor tool condition in real time. Experiments assessed cutting inserts in a milling head, both used and new. Results showed AE effectively diagnoses tool wear, with significant differences in signals from worn and new inserts. Fast Fourier Transform (FFT) analysis determined the frequency range of signals during machining, confirming AE's usefulness. Microscope verification supported the AE findings on tool wear. This research highlights AE's potential in non-destructive diagnostics, enhancing production efficiency and product quality
Keywords: Acoustic Emission (AE); Tool Wear Detection; Non-Invasive Diagnostics; Signal Analysis; Cutting Inserts